NUTRIENT AND ORGANIC MATTER REMOVAL FROM CHICKEN MANURE LEACHATE USING CHLORELLA SPP. - DINCĂ, Zamfira; HOAGHIA, Maria-Alexandra; TÖRÖK, Anamaria Iulia; KOVACS, Eniko; CADAR, Oana; NEAG, Emilia; ROMAN, Cecilia (Studia Universitatis Babeș-Bolyai Chemia, 2021)
In the present study, the use of chicken manure leachate (CML) as a nutrient source for the cultivation of Chlorella spp. at laboratory scale was investigated. The concentration of total organic carbon (TOC) and biochemical oxygen demand (BOD) was monitored during 15 days of cultivation in CML. The changes of pH, conductivity, Cl-, PO43-, SO42-, NO2- and NO3- concentrations were measured during the growth period. The BOD and TOC reduction was 96.4% and 86.1%, respectively after 15 days of cultivation in CML. The Chlorella spp. biomass cultured in CML had a high protein content compared to the biomass grown in the BG-11 medium. The obtained results suggest the potential use of CML as a nutrient source for the growth of Chlorella spp.